Pengembangan Pengolahan Kripik Opak di Desa Durin Barat Kecamatan Konang Kabupaten Bangkalan - Abdurrahman; Zakka, Umar (PT. Cahya Edupreneur Indonesia, 2024)
Creativity is an important thing in today's era, in this increasingly developing era. In fact, nowadays, there are still many people who do not increase their creativity, resulting in a decline in market prices, for example, the people of West Durin who do not increase their creativity in developing existing natural resources. The main problems of this research are: 1. What is the impact of the lack of creativity of the people of West Durin in managing natural resources? 2. What solutions do KKN participants provide to these problems? This research method uses the form of Action Research. Meanwhile, in community service, the Participatory Action Research (PAR) method is used, namely being fully involved and involving one party to contribute to the other party to make changes and improvements. The final conclusion of this research is that the impact of society's lack of creativity is a decrease in market prices, considering that society has its own products but does not have distinctive characteristics, both in terms of shape, flavor variants and packaging. The KKN participants provided educational studies on how to develop markets and socialize as well as interesting manufacturing practices by utilizing existing goods, both in terms of shape, flavor variants and packaging, as well as giving product names to become their own characteristics.